Pelatihan Program Pembelajaran Berbasis Industri di SMK Bhakti 1 Jombang - Moch. Syaiful Anwar; Mochamad Shaleh; Bambang Triono (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This community service program aims to strengthen vocational high school students’ understanding of industry-based learning through the reinforcement of thermodynamics concepts. The program was conducted at SMK Bhakti 1 Jombang on October 24–25, 2023, involving 20 students. The implementation methods included preparation, material delivery, Focus Group Discussion (FGD), and evaluation. The training was designed not only to enhance students’ understanding of basic thermodynamics but also to connect the concepts with industrial applications and everyday contexts. The results indicate an improvement in students’ conceptual understanding as well as higher engagement during the learning process. Through group discussions, students were also able to develop simple project ideas that link theory to practical application. The activity demonstrates that industry-based learning approaches can enhance students’ readiness for the workforce. Overall, this program had a positive impact on improving students’ conceptual comprehension and applied thinking skills in vocational education.